Analysis of Groundwater Resources in the Kyrgyz Republic - KARIMOV, Tashmukhamed Kh.; ABDYKALYKOV, Akymbek A.; KARIMOVA, Malika T.; KYZY, Nazira BAIGAZY; MAATKULOVA, Janyl (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
The relevance of this article is beyond doubt since the groundwater resources of the Kyrgyz Republic are very important for providing the population with drinking water. The article provides an analysis of groundwater reserves in the Kyrgyz Republic. The volumes and conditions of groundwater are given. On the territory of Kyrgyz Republic over its entire area, natural underground “lakes” are widespread. Determined the depth of groundwater reserves. Groundwater distribution flows were described. Groundwater contamination by nitrates and nitrites has been identified. Unsystematic creation of frequent water intakes, lack of monitoring of their operation can lead to aggravation of the situation with groundwater, lead to increased pollution and depletion processes. Since this topic has previously been little studied, the novelty of this article lies in the fact that the authors analyzed the causes of pollution of groundwater and offered their own ways to solve this problem.